2014
DOI: 10.1007/s13762-014-0605-0
|View full text |Cite
|
Sign up to set email alerts
|

An insight into microbial lipases and their environmental facet

Abstract: Lipases are serine hydrolases that catalyze the hydrolysis and synthesis of esters formed from glycerol and long-chain fatty acids, by acting at the oil-water interface. Lipases from microbial sources have received heightened attention for an array of industrial applications, and these enzymes have been well exploited in the environmental sector as well. In this article, we present an overview of microbial lipase, including the microorganisms from which it could be produced; the application of recombinant DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 199 publications
(163 reference statements)
2
24
0
Order By: Relevance
“…Their production is greatly influenced by medium composition besides physicochemical factors such as temperature, pH, and dissolved oxygen . More details on microbial lipases can be noted from recently reported review papers covering the overview on microbial lipases, microbial alkaline lipases, and purification of microbial lipases . Further, it has been recently revealed that microbial lipases can also be obtained through fermentation of agricultural waste and dairy waste contributing to the environmental protection and they may be exploited for future bio‐catalytic applications.…”
Section: Sources Of Lipasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Their production is greatly influenced by medium composition besides physicochemical factors such as temperature, pH, and dissolved oxygen . More details on microbial lipases can be noted from recently reported review papers covering the overview on microbial lipases, microbial alkaline lipases, and purification of microbial lipases . Further, it has been recently revealed that microbial lipases can also be obtained through fermentation of agricultural waste and dairy waste contributing to the environmental protection and they may be exploited for future bio‐catalytic applications.…”
Section: Sources Of Lipasesmentioning
confidence: 99%
“…The skimmed fat‐rich impurities can be easily digested by using lipases from C. rugosa , Pseudomonas, Bacillus , Acinetobacter , etc . Although anaerobic processes employing lipases are widely applied in the treatment of industrial wastewaters, food waste, dairy waste, grease from wool, manure, and waste water from oil mills . Cultivating lipase‐producing bacteria and seeding them in the effluents also helps in treating effluents originating from food processing, tannery, automobile industries, restaurant and fast‐food outlets .…”
Section: Applications Of Lipase‐catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, an alternative strategy of enzymatic hydrolysis could be applied to bring about lipid hydrolysis and improve biological treatment efficiency. Lipase‐producing microbial strains find promising applications in this arena …”
Section: Introductionmentioning
confidence: 99%
“…Lipase-producing microbial strains find promising applications in this arena. 4 Lipases (triacylglycerol acylhydrolases, EC. 3.1.1.3) are serine hydrolases that catalyze the hydrolysis of esters formed from glycerol and LCFA.…”
Section: Introductionmentioning
confidence: 99%